Archaeological Survey of Sīnīya Island, Umm al-Quwain - Power, Timothy; Borgi, Federico; Degli Esposti, Michele; Hoyland, Robert; Kannouma, Rania Hussein (Études et Travaux, 2022)
The preliminary results of a comprehensive survey of Sīnīya Island in the Khawr al-Bayḍāʾ of Umm al-Quwain are presented here. The onset of human occupation remains to be confirmed, with scarce evidence for limited activity in the late pre-Islamic period (LPI, c. 300 BC – AD 300). The first major phase of occupation dates to the seventh and eighth centuries (early Islamic period) when a monastery and settlement were established in the north-east of the island. Probably the peak occupation falls between the fourteenth and fifteenth centuries, when the stone-town of Old Umm al-Quwain 1 was built, followed by the eighteenth to early nineteenth century when the settlement moved to neighbouring Old Umm al-Quwain 2. The town was destroyed by the British in 1820 and moved to the facing tidal island, where Old Umm al-Quwain 3 (the modern city of the same name) developed. This resulted in an emptying of the landscape, and Sīnīya Island was little visited in the nineteenth and twentieth centuries, except for the estate of the ruling Āl Muʿallā represented by the Mallāh Towers.